Effect of Professional Attributes on Professional - Life Conflict : Gender as a Moderator in the Indian IT Industry - Thriveni Kumari, K. (Prabandhan: Indian Journal of Management, 2020)
The paper perceived the moderating role of gender on professional attributes with professional-life conflict (PLC). The study was drawn with a sample of 319 techie employees working in different IT sectors across India. Professional attributes were found as important elements that influence PLC. Gender, as a moderator in this relationship, showed the influence of interaction with few professional attributes only. The findings in the study suggested that there was a relationship between professional attributes and PLC and they influenced PLC based on time, strain, and behavior. Irrespective of the gender (male/female) in the IT sector, it affected on the relationship between the attributes and conflict. The implications of the study were discussed and the need for further research was also highlighted in the study.